Flypaper Effect pada Dana Alokasi Umum (DAU) dan Pendapatan Asli Daerah (PAD) terhadap Belanja Daerah pada Kabupaten/Kota di Pulau Sumatera - Mutiara Maimunah; Rusdi Akbar (The Indonesian Journal of Accounting Research, 2013)
The main objective of this research is to provide empirical proof of occurrence of flypaper effect in DAU and PAD on local expenditure in regencies/municipality in Sumatera. The other objective is to examine existence of different flypaper effect between low-PAD region and high-PAD region. Then, it examined whether or not flypaper still occurred in local expenditures in education, health and infrastructure field. Data was from local budget and revenue report. Result of analysis indicates that DAU and PAD separately influenced local expenditure. However, when tested at once, PAD indicated no significant result. It indicates that there have occurred flypaper effects. Flypaper effect is defined as local response (expenditure) that is greater than transfer (Oates, 1999). Result of test to examine whether or not flypaper effects that tend to increase amount of local expenditure is significant. That is, the condition tend to make local government just wait what DAU allocation they receive before determining their expenditure (Sukriy & Halim, 2004), so the next period expenditure tend to be greater. Flypaper effect is indifferent in regions whose PAD is low compared with region whose PAD is high. It means that the condition (flypaper effect) in low PAD regions is as strong as in high PAD regions. When testing local expenditure related to public, only expenditure in education field did not undergo flypaper effect, while in health and infrastructure expenditure the condition still occurred. The results still require confirmation through future researches.